PSO based automatic weight selection and fixed structure robust loop shaping control for power system control applications - Kaitwanidvilai, Somyot; Olranthichachart, Piyapong; Ngamroo, Issarachai (My University, 2011)
This paper proposes a new technique to design a fixed-structure robust loop shaping controller for the power system control applications. The proposed technique uses Particle Swarm Optimization (PSO) to find the optimal controller parameters so that the stability margin of controlled system is maximized. Infinity norm from disturbances to states is formulated as the cost function in our optimization. In addition, weighting function, which is normally difficult to obtain, is automatically determined by PSO. In this paper, the proposed technique is adopted to design the robust controllers for both two areas interconnected power system and VAR compensator connected electric power system. The performance of the proposed controller is investigated in comparison with conventional H∞ loop shaping controller, robust controller designed by LMI method and reduced order robust controller by Hankel norm model reduction method. As results indicated, the stability margin of the proposed controller is better than that of the controller designed by LMI method and the reduced order robust controller. In addition, the order of the proposed controller is much lower than that of the conventional robust loop shaping controller, making it easy to implement in practical works. ICIC International © 2011.
Keywords: Fixed-structure robust loop shaping control; H∞ loop shaping control; Particle swarm optimization